Globalization Substance And Industrial Revolution 4.0 And The Role Of Technological Innovation For Economic Development Towards Entrepreneurship - Muhammad Ade Kurnia Harahap; Rully Novie Wurarah; Apit Fathurohman; Amat Suroso; Yusuf Iskandar (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
Entrepreneurship in the 21st century is characterized by a high volume of flexibility and knowledge. The two features have gained a great and renewed relevance as competitive advantages in a globalized economy. The classical industry structure has transitioned into a smaller focus and higher decentralization which is a major indicator of global development. Global competition has increased as technology changes due to the rise of economic liberalization. Today, there is a belief that fostering a nation's competitiveness translates into fostered entrepreneurship. The fourth industrial revolution has brought in technological innovation, therefore, spurring a transformation in production. There are two facets to this transformation. One, the need to integrate and upgrade systems, and two, the emergency of new systems based on artificial intelligence technology. The increased application of technology speeds up the restructuring and structural upgrading of the global industrial chain, therefore, enhancing the spirit of entrepreneurship. The purpose of this paper is to review the literature on the globalization substance, industrial revolution 4.0, and the role of the associated technological innovation for economic development towards entrepreneurship. First, the paper will present a theoretical background of these phenomena synthetically from globalization, industrial revolution phases, associated technological innovation and milestones in economic growth, and their role in enhancing entrepreneurship. The paper will highlight the role of technology-driven profile in the new global economy, spearheaded by innovative business strategies towards entrepreneurial initiatives.